2018
DOI: 10.1136/bjophthalmol-2018-312774
|View full text |Cite
|
Sign up to set email alerts
|

Cilioretinal artery hypoperfusion and its association with paracentral acute middle maculopathy

Abstract: Background/aimsTo study the multimodal imaging findings of a large series of eyes with cilioretinal artery obstruction (CILRAO) and describe the systemic associations.MethodsMulticentre, retrospective chart review from 12 different retina clinics worldwide of eyes with CILRAO, defined as acute retinal whitening in the distribution of the cilioretinal artery, were identified. The clinical, systemic information and multimodal retinal imaging findings were collected and analysed.ResultsA total of 53 eyes of 53 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…closer to the involved artery), hyperreflectivity of both middle and inner retinal layers in B-scan OCT with a globular pattern in en face OCT is observed. Recent studies revealed that micro vortex-like structures in DCP were responsible for venous drainage of middle retinal layers and behaved as a watershed zone area [18][19][20]. Meticulous scrutiny of en face OCT and OCTA imaging has demonstrated that PAMM, whether isolated or not, heralds an ischemic cascade, which begins as a fernlike configuration with a propensity to venular pole at the level of DCP and progresses laterally to the center of ischemia, producing globular pattern.…”
Section: Discussionmentioning
confidence: 99%
“…closer to the involved artery), hyperreflectivity of both middle and inner retinal layers in B-scan OCT with a globular pattern in en face OCT is observed. Recent studies revealed that micro vortex-like structures in DCP were responsible for venous drainage of middle retinal layers and behaved as a watershed zone area [18][19][20]. Meticulous scrutiny of en face OCT and OCTA imaging has demonstrated that PAMM, whether isolated or not, heralds an ischemic cascade, which begins as a fernlike configuration with a propensity to venular pole at the level of DCP and progresses laterally to the center of ischemia, producing globular pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Recent enface OCT imaging and OCTA studies have shown that micro vortex-vein like structures are available in the deep capillary plexus and these structures are responsible for the drainage of the middle retinal layers, so any occlusion in front of the venous pathway can predominantly affect this area and secondary PAAM can be seen here [4][5][6]8]. So, it seems that deep capillary plexus is a sensitive structure for both arterial and venous insufficiencies and multimodal imaging studies can show this vulnerability to vascular disturbances.…”
Section: Discussionmentioning
confidence: 94%
“…As opposed to the central retinal artery, the cilioretinal artery arises from the peripapillary choroid or directly from one of the short posterior ciliary arteries and isn't liable to autoregulation. Subsequently, a drop in systemic blood pressure may cause a secondary reduction in the perfusion pressure and relative hypoperfusion or insufficiency of the cilioretinal artery [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The cilioretinal artery (CILRA) can be found in one third of normal eyes. 1 This artery originates from the choroid or from one of the short posterior ciliary arteries. 1,2 Conditions of its obstruction (cilioretinal artery obstruction (CILRAO) have been historically subdivided into three groups: (a) CILRAO isolated, (b) CILRAO associated with retinal vein occlusions, and (c) CILRAO associated with giant cell arteritis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Conditions of its obstruction (cilioretinal artery obstruction (CILRAO) have been historically subdivided into three groups: (a) CILRAO isolated, (b) CILRAO associated with retinal vein occlusions, and (c) CILRAO associated with giant cell arteritis. 1…”
Section: Introductionmentioning
confidence: 99%